Analisis Manajemen Risiko pada Toko Sembako Skala UMKM di Kelurahan Kraton Kota Tegal - Tri Handayani, Larasati; Amirah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to analyze the types of risks faced by MSME-scale grocery stores in the Kraton sub-district, Tegal City, and formulate mitigation strategies that are appropriate to the business conditions. The research method used a qualitative descriptive approach through direct observation and structured interviews with grocery store owners, supported by a questionnaire covering risk identification, risk measurement, and risk management. The results show that the main risks faced include supply risks such as dependence on a single supplier and price fluctuations, financial risks in the form of unstable cash flow and unsystematic financial records, operational risks related to recording errors and damage to goods, and marketing risks due to price competition and changes in consumer behavior. In conclusion, the implementation of structured risk management through supplier diversification, more organized stock and financial records, and adaptation of marketing strategies is necessary to improve the resilience of grocery stores amid economic dynamics and market changes.